2020
DOI: 10.1016/j.mayocp.2020.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Migraine on Pregnancy Planning: Insights From the American Registry for Migraine Research

Abstract: Objective: To evaluate the effect of migraine on women's pregnancy plans. Patients and Methods: Participants were enrolled in the American Registry for Migraine Research, an observational study that recruits patients from headache specialty clinics across the United States. Data for this analysis were collected via patient-completed questionnaires completed from February 1, 2016, through September 23, 2019. Participants were adult women with migraine who answered the American Registry for Migraine Research fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
25
0
3
Order By: Relevance
“…Primary headaches, comprising migraine, tension headache, cluster headache, and other trigeminal autonomic cephalgias (TACs), are common during pregnancy, affecting 10%–17% of pregnancies 1 . A recent survey of women with migraine across the United States found that approximately one in five women avoided pregnancy because of migraine; chief concerns noted were that the migraine could worsen during pregnancy (73% of women) or negatively affect their child's development (76%) 2 . Although tension headaches are the most common primary headache during pregnancy, migraine is by far the most common primary headache to present to clinical practice, accounting for about 90% of primary headache‐related visits to providers during pregnancy 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary headaches, comprising migraine, tension headache, cluster headache, and other trigeminal autonomic cephalgias (TACs), are common during pregnancy, affecting 10%–17% of pregnancies 1 . A recent survey of women with migraine across the United States found that approximately one in five women avoided pregnancy because of migraine; chief concerns noted were that the migraine could worsen during pregnancy (73% of women) or negatively affect their child's development (76%) 2 . Although tension headaches are the most common primary headache during pregnancy, migraine is by far the most common primary headache to present to clinical practice, accounting for about 90% of primary headache‐related visits to providers during pregnancy 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent survey of women with migraine across the United States found that approximately one in five women avoided pregnancy because of migraine; chief concerns noted were that the migraine could worsen during pregnancy (73% of women) or negatively affect their child's development (76%). 2 Although tension headaches are the most common primary headache during pregnancy, migraine is by far the most common primary headache to present to clinical practice, accounting for about 90% of primary headache-related visits to providers during pregnancy. 3 The stresses of pregnancy and imminent infant care may exacerbate the frequency and severity of primary headaches.…”
Section: Introductionmentioning
confidence: 99%
“…The 6-stage are outlined as follows: (1) identification of the research question, (2) identification of relevant studies, (3) selection of studies, (4) charting of data, (5) summary of results and (6) consultation with stakeholders, an optional but recommended evaluation component of a ScR.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Headache has been linked to a significant impact on women quality of life [6]. The ScR of the efficacy of conservative physiotherapeutic approaches in hormonal-related headaches in this protocol will survey the current scientific literature to identify gaps in the research across contents and methods to encourage future research and uniformity of terms and prevent duplication of efforts.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
See 1 more Smart Citation